In Situ Transmission Electron Microscopy Analysis of Aluminum–Germanium Nanowire Solid-State Reaction - El hajraoui, Khalil (Nano Lett, 2019)
[Image: see text] To fully exploit the potential of semiconducting nanowires for devices, high quality electrical contacts are of paramount importance. This work presents a detailed in situ transmission electron microscopy (TEM) study of a very promising type of NW contact where aluminum metal enters the germanium semiconducting nanowire to form an extremely abrupt and clean axial metal–semiconductor interface. We study this solid-state reaction between the aluminum contact and germanium nanowire in situ in the TEM using two different local heating methods. Following the reaction interface of the intrusion of Al in the Ge nanowire shows that at temperatures between 250 and 330 °C the position of the interface as a function of time is well fitted by a square root function, indicating that the reaction rate is limited by a diffusion process. Combining both chemical analysis and electron diffraction we find that the Ge of the nanowire core is completely exchanged by the entering Al atoms that form a monocrystalline nanowire with the usual face-centered cubic structure of Al, where the nanowire dimensions are inherited from the initial Ge nanowire. Model-based chemical mapping by energy dispersive X-ray spectroscopy (EDX) characterization reveals the three-dimensional chemical cross-section of the transformed nanowire with an Al core, surrounded by a thin pure Ge (∼2 nm), Al(2)O(3) (∼3 nm), and Ge containing Al(2)O(3) (∼1 nm) layer, respectively. The presence of Ge containing shells around the Al core indicates that Ge diffuses back into the metal reservoir by surface diffusion, which was confirmed by the detection of Ge atoms in the Al metal line by EDX analysis. Fitting a diffusion equation to the kinetic data allows the extraction of the diffusion coefficient at two different temperatures, which shows a good agreement with diffusion coefficients from literature for self-diffusion of Al.